Towards Uniform Electrochemical Porosification of Bulk HVPE-Grown GaN. Issue 5 (1st January 2019) - Monaico, Ed.; Moise, C.; Mihai, G.; Ursaki, V. V.; Leistner, K.; Tiginyanu, I. M.; Enachescu, M.; Nielsch, K.
Abstract : In this paper, we report on results of a systematic study of porous morphologies obtained using anodization of HVPE-grown crystalline GaN wafers in HNO3, HCl, and NaCl solutions. The anodization-induced nanostructuring is found to proceed in different ways on N- and Ga-faces of polar GaN substrates. Complex pyramidal structures are disclosed and shown to be composed of regions with the degree of porosity modulated along the pyramid surface. Depending on the electrolyte and applied anodization voltage, formation of arrays of pores or nanowires has been evidenced near the N-face of the wafer. By adjusting the anodization voltage, we demonstrate that both current-line oriented pores and crystallographic pores are generated. In contrast to this, porosification of the Ga-face proceeds from some imperfections on the surface and develops in depth up to 50 μm, producing porous matrices with pores oriented perpendicularly to the wafer surface, the thickness of the pore walls being controlled by the applied voltage. The observed peculiarities are explained by different values of the electrical conductivity of the material near the two wafer surfaces.